Protes Perajin Tahu-Tempe Dalam Wacana Media: Sebuah Penelitian Awal Menggunakan Analisis Isi - Kresno Agus Hendarto (Conference In Business, Accounting, And Management (CBAM), 2012)
Tofu and tempe have popular among the Indonesia people. Nearly all people have ever consumed them. However with the long draught in the last half century in United States of America, the price of soybean, the raw material of tofu-tempe, has increased significantly. Consequently, the producers of tofu-tempe in Jakarta protested. They stopped the production for 3 days from 25 to 27 July 2012. The relation between media and protest is transactional. On the one hand, the protesting group uses media to disseminate their activities. On the other hand, media needs news to report. The objective of this study is to describe the protest of tofu-tempe producers. Therefore, this study attempts to answer some questions: (i) what is the root caused and what have triggered the protest? (ii) what is the target and what is the objective of the protest?; (iii) who is benefited by the protest?; and (iv) why the producers participated in the protest? Data on the protest by tofu-tempe producers were collected from media and analyzed by content analysis. The results showed that the root caused of the protest were (1) unability of the government to provide self-sufficiency of soybean; and (2) unability of the government to control the supply of soybean at national level; the trigger of the protest was significant increase of soybean price. They have made the producers protested. The objective of the protest was that consumers can understand why the price increased. The targets of the protest were the government; and the people most benefited by the protest were soybean importers.Keywords: protest, media, agenda setting, social dilemma theory, qualitative contentÂ analysis